Analisis Karakteristik Angkutan Penumpang: Studi Kasus: Bus Pariwisata di Kabupaten Tana Toraja - Muh. Alip Azhar Alwi; Hakzah Hakzah; Andi Bustan Didi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Passenger comfort in using public transportation is the main factor in satisfaction with the transportation services used. This lack of satisfaction will affect the use of transportation services which will reduce the income from transportation services. The aim of this research is to determine the characteristics, level of passenger/customer satisfaction based on (reliability, assurance, tangibles, empathy, responsiveness) and factors that influence the level of passenger satisfaction. This research uses a quantitative method, which was carried out in September-November 2022 at a tourist bus shelter in Tana Toraja Regency using SPSS analysis. The results of the research show that the analysis of 5 dimensions, namely tangibles (physical evidence) 0.131, reliability (reliability) 0.084, responsiveness (responsiveness) 0.082, confidence (belief) 0.117, empathy (attention) 0.0120. The most influential factor is the tangibles dimension (physical evidence), which is 0.131.